Assessing Creative and Cottage Industry towards Strengthen Local Knowledge of Local Craft Community in Malaysia - Norhayati HUSSIN; Nurul Syfa’ MOHD TOKIRAN; Masitah AHMAD; Mohd Sazili SHAHIBI (Communications of International Proceedings, 2022)
This paper addressed the current creative and cottage industry scenario to strengthen the local craft community's local knowledge, especially in East Coast Malaysia. The states have been chosen because their uniqueness and identity vary from other states in Malaysia. The available local craft product has been discussed further in identifying the similarity of local craft products in East Coast Malaysia. The similarity of the local craft product has been identified in East Coast Malaysia in discovering the craft that has significant value towards the local craft community in Malaysia. The identity of local craft products represents each state's culture and rich heritage, and the local content value should be appreciated in the current digital age. The songket weaving commonly available in East Coast Malaysia has been discussed, especially in terms of origin and pattern, to know the differences in songket weaving based on those states. The benefits of local content within Malaysia's cottage industry have been discovered and discussed in this paper.
Keywords: Information Science; Local Content; Rural Community; Cottage Industry